Individual differences and brain structure: correlates with magnetoencephalography - Hunt, Benjamin A.E. (2017)
The work presented in this thesis aims to increase clinical capacity for magnetoencephalography (MEG) by developing an understanding of how, in healthy participants, individual differences in brain structure, personality, and demographics influence measurements of neural oscillatory responses and functional connectivity. To this end, a large cohort of normative data was acquired using MEG with additional data acquisition using high-field MRI and supplementary individual difference data collected via a psychometric battery and screening questionnaire. MEG data were analysed to elucidate both primary sensory responses to stimulation and functional connectivity within task and task-free acquisitions.